The grand dark - Kadrey, Richard (HarperVoyager, an imprint of HarperCollinsPublishers, 2019)
The Great War is over. The city of Lower Proszawa celebrates the peace with a decadence and carefree spirit as intense as the war<U+2019>s horrifying despair. But this newfound hedonism<U+2014>drugs and sex and endless parties<U+2014>distracts from strange realities of everyday life: Intelligent automata taking jobs. Genetically engineered creatures that serve as pets and beasts of war. A theater where gruesome murders happen twice a day. And a new plague that even the ceaseless euphoria can<U+2019>t mask. Unlike others who live strictly for fun, Largo is an addict with ambitions. A bike messenger who grew up in the slums, he knows the city<U+2019>s streets and its secrets intimately. His life seems set. He has a beautiful girlfriend, drugs, a chance at a promotion<U+2014>and maybe, an opportunity for complete transformation: a contact among the elite who will set him on the course to lift himself up out of the streets. But dreams can be a dangerous thing in a city whose mood is turning dark and inward. Others have a vision of life very different from Largo<U+2019>s, and they will use any methods to secure control. And in behind it all, beyond the frivolity and chaos, the threat of new war always looms.